CFD-Based Investigation of Static and Dynamic Pressure Effect in Aerostatic Bearings with Annular Grooves at High Speed - Wentao Song; Minggui Li; Peng Cheng; Decheng Wang; Chenxi Shao; Junying Zhou (Lubricants)
Based on the SST k-ω turbulence model, this study investigated the flow fields of annular groove and non-groove small-hole throttling aerostatic bearings (AGSTABs and STABs). It examined the formation mechanisms of static and dynamic pressure effects in both flow fields at high speed, evaluating how parameters such as eccentricity, groove width ratio, and depth ratio influence the average load capacity and static and dynamic pressure effects. The findings show that STABs combine static and dynamic pressure effects at high speeds, while AGSTABs decouple them to enhance load capacity, simultaneously reducing vortex and backflow intensity. At low eccentricities, AGSTABs exhibit superior performance over STABs, achieving 20% higher average load capacity at 0.1 eccentricity. Additionally, increasing eccentricity enhances static and dynamic pressure effects in both bearings. A larger groove width ratio decreases the throttling efficiency and dynamic pressure, with pressure dropping from 3.5 MPa (static) to 1.6 MPa, and 6.3 MPa (dynamic) to 1.7 MPa respectively, at 30,000 RPM. In contrast, the depth ratio of annular groove has only a minor impact on static and dynamic pressure effects.